Inequality, Coalitions and Collective Action - Pranab Bardhan; Nirvikar Singh (University of California, Economics Department, 2004)
In a model where cooperation is beneficial, but subject to cheating, and is supported by trigger strategy punishments in a repeated game, we explore the relationship between the nature of cooperation (size and composition of coalitions) and underlying inequality in the distribution of private productive assets.
Keywords: 330; inequality; self-enforcing; collective action; infrastructure